Pneumonia Risk Stratification Scores for Children in Low-Resource Settings: A Systematic Literature Review - Deardorff, Katrina V. (Pediatr Infect Dis J, 2018)
BACKGROUND: Pneumonia is the leading infectious cause of death among children less than five years of age. Predictive tools, commonly referred to as risk scores, can be employed to identify high-risk children early for targeted management to prevent adverse outcomes. This systematic review was conducted to identify pediatric pneumonia risk scores developed, validated, and implemented in low-resource settings. METHODS: We searched CAB Direct, Cochrane Reviews, Embase, PubMed, Scopus, and Web of Science for studies that developed formal risk scores to predict treatment failure or mortality among children less than five years of age diagnosed with a respiratory infection or pneumonia in low-resource settings. Data abstracted from articles included location and study design, sample size, age, diagnosis, score features and model discrimination. RESULTS: Three pediatric pneumonia risk scores predicted mortality specifically, and two treatment failure. Scores developed using World Health Organization recommended variables for pneumonia assessment demonstrated better predictive fit than scores developed using alternative features. Scores developed using routinely collected healthcare data performed similarly well as those developed using clinical trial data. No score has been implemented in low-resource settings. CONCLUSIONS: While pediatric pneumonia-specific risk scores have been developed and validated, it is yet unclear if implementation is feasible, what impact, if any, implemented scores may have on child outcomes, or how broadly scores may be generalized. To increase the feasibility of implementation, future research should focus on developing scores based on routinely collected data.